A Large Orthokeratinized Odontogenic Cyst of the Maxilla: A Rare Case Report - Mehdizadeh , Mohammad; Lotfi, Ali; Atarbashi Moghadam, Saede (Journal of Dental School, 2023)
Objectives Orthokeratinized odontogenic cysts (OOCs) are relatively uncommon odontogenic cysts, lined by an orthokeratinized epithelium. These cysts show different clinical behaviors from the more common odontogenic keratocysts (OKCs), and it is important to distinguish these two types of cysts. Commonly, OOCs manifest as well-defined, unilocular, radiolucent lesions, with a high frequency in the mandibular region. In this case report, we aimed to describe a large maxillary OOC with prominent tooth displacement. Case The patient was a 14-year-old boy with significant painless swelling in the upper jaw. The panoramic radiograph revealed a well-defined, unilocular radiolucent area from midline to the first right maxillary molar with prominent tooth displacement. The lesion was completely excised under local anesthesia. The histopathological sections demonstrated a cystic lesion lined by an orthokeratinized stratified squamous epithelium with a prominent granular cell layer. Conclusion Based on the present results, OOCs can be large in size and may be characterized by ballooning expansion and tooth displacement. Therefore, knowledge of the clinical and radiographic features of these uncommon odontogenic cysts can facilitate an accurate diagnosis.